An insight into thermal, chemical, and structural characterization of biopolymers - Tilottoma Kargupta; N Pooja; Md. Hafizur Rahman; Inesh Vij; Rajib Biswas; Sanchita Roy; Nirmal Mazumder (Discover Applied Sciences)
Abstract Bioplastics have been identified as an eco-friendly substitute for conventional plastics. These bioplastics can be customized according to their usage and availability of raw materials. Bioplastics must undergo certain characterization tests to ensure that their properties and integrity are maintained under set conditions. This is accomplished by testing different parameters, such as surface morphology and thermal, chemical, and structural properties. In this review, we elaborate on the various techniques used to study these parameters while also providing brief insight into the ways in which they have been used thus far.